Interest and self motivation as correlates of capacity building and career commitment: a study of female librarians in Nigeria (2013)
The study investigated Interest and Self Motivation as Correlates of Capacity Building and Career Commitment of Female Librarians in Nigeria. This was with a view to providing valuable data for stakeholders to guide in organizing career development progammes. The survey method of research was adopted for the study and the instrument for collecting data were the questionnaire, interview and focus group discussion. Findings of the study revealed that majority of female librarians in Nigeria never were interested in the profession before going in for it, but are now that they are in the field and are committed to their career to a great extent. However, their capacity building opportunities and efforts are very low. Therefore, the study recommends that the Nigerian Library Association (NLA) and other Organizers of Conferences and workshops for Librarians should make the dues affordable; arrange more training outlets and make workshops more of practical training sessions. Also, stakeholders of institutions with libraries should endeavor to make fund available for the provision of ICT infrastructure and platform, acquisition of current professional literatures on librarianship etc.